Aphid management - Hermoso-De-Mendoza, Alfonso; Belliure, Belén; Llorens, J. M.; Marcos, María A.; Michelena, José Manuel (Cajamar Caja Rural, 2020)
Belonging to the superfamily Aphidoidea, aphids are Hemiptera insects, many of the species causing economic damage to most cultivated plants. This occurs directly, when they suck the sap and weaken the plants, or indirectly through the transmission of several plant diseases, especially of a viral nature. Aphids cause this plant damage using their biter-sucker mouth, as all the Hemiptera (MIYAZAKI, 1987b). The labium has been modified, taking the shape of a wide canal mouth (rostrum or proboscis) that encloses four thin stylets, which are developed from the two maxillae and the two mandibles, forming an elongated filament, which contains two ducts. The insect, after piercing the plant with its stylets, will inject the saliva through one of the ducts (the salivary canal) in order to dissolve the sap, while the other duct (the food canal) is used for absorbing the sap once it has been dissolved. This feeding system explains the Hemiptera capacity (and particularly, the aphid capacity) to transmit viruses or other type of pathogens: when they suck the fluids of a sick plant, the insects acquire the virus and later, when they inject the sap into a healthy plant, they infect it with the virus acquired.